The role of the right atrium in development of postoperative atrial fibrillation: A speckle tracking echocardiography study. Issue 8 (17th May 2019) - Aksu, Uğur; Kalkan, Kamuran; Gulcu, Oktay; Aksakal, Emrah; Öztürk, Mustafa; Topcu, Selim
Abstract: Purpose: Atrial fibrillation (AF) is relatively frequent in the postoperative period, and is associated with an increased frequency of adverse events. The role of right atrial (RA) volume and functions in the development of AF is unknown. In this study, we investigated the effect of RA echocardiographic indices on AF development in the postoperative period. Method: We enrolled 142 consecutive patients who underwent coronary artery bypass surgery, and assigned them into two groups depending on the occurrence or not of AF development in the postoperative period. Results: A propensity score matching analysis was performed to balance the groups, and 37 pairs were eventually included in the analysis. The median age was 67.5 (63‐75) years and 73.3% of them were males. In the univariate analysis, right atrial volume index (RAVi), right atrial strain during reservoir phase (RASr), left ventricular global longitudinal strain, right ventricular strain, left atrial volume index, left atrial strain during reservoir phase, and systolic pulmonary artery pressure were associated with AF development. In the regression analysis, we found that RAVi (OR: 3.1, 95% CI: 2.2‐6.3, P : .033) and RASr (OR: 0.82, 95% CI: 0.67‐0.93, P : .048) were independent predictors of AF development. Conclusions: RA structure and functions are closely associated with AF development in the postoperative period, and screening of RA functions prior to surgery may be useful for preventing AF development.